Push-out bond strength and intratubular biomineralization of a hydraulic root-end filling material premixed with dimethyl sulfoxide as a vehicle - Ju-Ha Park; Hee-Jin Kim; Kwang-Won Lee; Mi-Kyung Yu; Kyung-San Min (Restorative Dentistry & Endodontics)
ObjectivesThis study was designed to evaluate the parameters of bonding performance to root dentin, including push-out bond strength and dentinal tubular biomineralization, of a hydraulic bioceramic root-end filling material premixed with dimethyl sulfoxide (Endocem MTA Premixed) in comparison to a conventional powder-liquid–type cement (ProRoot MTA).Materials and MethodsThe root canal of a single-rooted premolar was filled with either ProRoot MTA or Endocem MTA Premixed (n = 15). A slice of dentin was obtained from each root. Using the sliced specimen, the push-out bond strength was measured, and the failure pattern was observed under a stereomicroscope. The apical segment was divided into halves; the split surface was observed under a scanning electron microscope, and intratubular biomineralization was examined by observing the precipitates formed in the dentinal tubule. Then, the chemical characteristics of the precipitates were evaluated with energy-dispersive X-ray spectroscopic (EDS) analysis. The data were analyzed using the Student’s t-test followed by the Mann-Whitney U test (p < 0.05).ResultsNo significant difference was found between the 2 tested groups in push-out bond strength, and cohesive failure was the predominant failure type. In both groups, flake-shaped precipitates were observed along dentinal tubules. The EDS analysis indicated that the mass percentage of calcium and phosphorus in the precipitate was similar to that found in hydroxyapatite.ConclusionsRegarding bonding to root dentin, Endocem MTA Premixed may have potential for use as an acceptable root-end filling material.